النظرة المعرفية للوجود في العرفان - عبد العزيز عباسي (Sekolah Tinggi Agama Islam Sadra, 2014)
Knowledge of the universe is one of the three necessary types of knowledge, i.e.: knowledge of God, knowledge of the Soul and knowledge of the universe. Most of the time we refer to it as (Mabdaa) or the Origin; how the world is created. Or what is known in theology as Creation ex nihilo: where creatures are distinct from their creator who is the First Cause, or in illuminative philosophy as Emanation where creatures pre-existed within the essence of their origin by flowing as a consequence of perfection. So we are confronted with different theories about the universe where so some views will underlie oneness of being while others multiplicity, and in both case we need to explain and justify any resulting theory. So the purpose of this article is to provide a concise explanation about the knowledge related to the universe and tries to justify the claimed oneness of Being in mysticism.